Lucky for good - Patron, Susan, 1948- (Atheneum Books for Young Readers, 2011)
The residents of Hard Pan, California, come together to help Brigitte and Lucky when the County Health Department threatens to close down the café, and meantime Miles's life is complicated by his mother's return.